Effects of Saccharomyces cerevisiae in broiler diets: 2. Meat rheological properties and consumer perception - Branciari, Raffaella; Ranucci, David; Forte, Claudio; Acuti, Gabriele; Miraglia, Dino; Olivieri, Oliviero; Trabalza-Marinucci, Massimo (Progress in Nutrition, 2014)
The aim of this work was to evaluate the effect inactivated Saccharomyces cerevisiae dietary supplementation on poultry meat quality and consumer expectation. Four groups of broilers were fed different diets as follows: control commercial diet enriched with conjugated linoleic (CLA) and ω3 polyunsaturated fatty acids (group C); C added with 150 mg/kg vitamin E (group E); C added with 1,5 g/kg inactivated yeast (group Sc); C added with vitamin E (150 mg/kg) and inactivated yeast (1,5 g/kg) (group ScE). A higher cooking loss, compared to control, was recorded in the ScE group. The shear force test showed higher values for the ScE group compared with the others experimental treatments. The blind consumer test revealed no difference in the sensory parameters considered amongst groups. A marked influence of information (informed test) on the perception of meat quality was observed: higher values for the ScE group and decreased values for the control group were recorded.